Self-perception of mental health, COVID-19 and associated sociodemographic-contextual factors in Latin America - Pablo Roa; Guillermo Rosas; Gloria Isabel Niño-Cruz; Sergio Mauricio Moreno-López; Juliana Mejía-Grueso; Haney Aguirre-Loaiza; Javiera Alarcón-Aguilar; Rodrigo Reis; Adriano Akira Ferreira Hino; Fernando López; Deborah Salvo; Andrea Ramírez-Varela (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
Abstract This study aimed to estimate the prevalence of alterations in self-perceived mental health during the COVID-19 pandemic and their associated factors in four Latin American countries. This is a cross-sectional study based on data collected from adults in 2021 through the Collaborative Response COVID-19 Survey by the MacDonnell Academy at Washington University in St. Louis (United States). The sample was composed of 8,125 individuals from Brazil, Colombia, Mexico, and Chile. A generalized linear model for a binary outcome variable with a logistic link and fixed country effects was used. There were 2,336 (28.75%) individuals who considered having suffered alterations in self-perceived mental health. Unemployed individuals (OR = 1.40; 95%CI: 1.24-1.58), those with bad/regular quality of life (OR = 5.03; 95%CI: 4.01-6.31), and those with high socioeconomic status (OR = 1.66; 95%CI: 1.41-1.96) had a higher risk of self-perceived mental health alterations than those with full-time employment, excellent quality, and low socioeconomic status. According to the fixed-effects model, Brazilians living in the country during the pandemic, who disagreed with their government's decisions (OR = 2.05; 95%CI: 1.74-2.42) and lacked trust in their government (OR = 2.10; 95%CI: 1.74-2.42) had a higher risk of having self-perceived mental health alterations. Nearly 30% of respondents indicated that the COVID-19 pandemic altered their self-perceived mental health. This outcome was associated with political, sociodemographic, and health risk factors. These findings should help policymakers develop post-pandemic community interventions.